Neural Correlates of Auditory Figure-Ground Segregation Based on Temporal Coherence - Teki, Sundeep; Barascud, Nicolas; Picard, Samuel; Payne, Christopher; Griffiths, Timothy D.; Chait, Maria (Cerebral cortex (New York, N.Y. 1991), 2016)
To make sense of natural acoustic environments, listeners must parse complex mixtures of sounds that vary in frequency, space, and time. Emerging work suggests that, in addition to the well-studied spectral cues for segregation, sensitivity to temporal coherence-the coincidence of sound elements in and across time-is also critical for the perceptual organization of acoustic scenes. Here, we examine pre-attentive, stimulus-driven neural processes underlying auditory figure-ground segregation using stimuli that capture the challenges of listening in complex scenes where segregation cannot be achieved based on spectral cues alone. Signals ("stochastic figure-ground": SFG) comprised a sequence of brief broadband chords containing random pure tone components that vary from 1 chord to another. Occasional tone repetitions across chords are perceived as "figures" popping out of a stochastic "ground." Magnetoencephalography (MEG) measurement in naïve, distracted, human subjects revealed robust evoked responses, commencing from about 150 ms after figure onset that reflect the emergence of the "figure" from the randomly varying "ground." Neural sources underlying this bottom-up driven figure-ground segregation were localized to planum temporale, and the intraparietal sulcus, demonstrating that this area, outside the "classic" auditory system, is also involved in the early stages of auditory scene analysis."